Salting‐out extraction of sinomenine from Sinomenium acutum by an alcohol/salt aqueous two‐phase system using ionic liquids as additives. Issue 7 (31st May 2017) - Li, Fenfang; Li, Qiao; Wu, Shuanggen; Sun, Danyu; Tan, Zhijian
Abstract: BACKGROUND: The aqueous two‐phase extraction (ATPE) based on organic solvent and inorganic salt was considered a promising method in the extraction, enrichment, and purification field. Ionic liquids (ILs) used as additives to the aqueous two‐phase system (ATPS) can improve the extraction yield. RESULTS: In this study, seven ILs were added to the ethanol/ammonium sulfate ATPS and used for the salting‐out extraction (SOE) of sinomenine from Sinomenium acutum . The IL [C2 OHmim]FeCl4 was screened as the optimal additive, then the influencing factors IL amount, ethanol concentration, salt concentration, and temperature were investigated. The maximum extraction efficiency of 96.4% was obtained under the following conditions: 23.06 wt% ethanol concentration, 27.28 wt% (NH4 )2 SO4 concentration, 4.0 wt% [C2 OHmim]FeCl4 and 40 ° C temperature. Moreover, the components in the SOE system can be recycled after extraction. CONCLUSION: Thus, this ATPS had lower cost and higher extraction ability, and it is feasible to scale up using a small amount of ILs. This system can also be used in the extraction of some other important active compounds from natural plant resources. © 2017 Society of Chemical Industry